Pengaruh Literasi Keuangan dan Orientasi Pasar Terhadap Kinerja UMKM - Virgia, Tasya; Meirina, Elsa (Universitas Multi Data Palembang, 2023)
Recognizing the importance of micro, small and medium enterprises, the government is committed to continuing to encourage and develop them. This commitment should be a shared responsibility between the central and regional governments. Pesisir Selatan Regency is one of 19 regencies/cities in West Sumatra which is very aggressively encouraging the revival of micro, small and medium enterprises in the area. The purpose of this study was to examine the effect of financial literacy and market orientation owned by micro, small and medium enterprises on the performance of micro, small and medium enterprises. Quantitative research methods were used in this study with questionnaires as a data collection tool. A total of 88 questionnaires were collected from micro, small and medium enterprises in IV Jurai District. Sample calculation using slovin formula. Data processing using the SPSS application. The results of the study show that financial literacy has a positive effect while orientation has a negative effect on the performance of MSMEs. In accordance with the formulation of the hypothesis, it is concluded that financial literacy and market orientation affect the performance of Micro, Small and Medium Enterprises.